Praktik Kebijakan Utang Dalam Negeri Dan Luar Negeri Indonesia Dalam Tinjauan Ekonomi Islam - Amaliyah Sholikha; Sagitha Febi Wulandari; Nabilah Khairunnisa; Ade Nur Rohim (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
Taking debt is not a negative thing, but in practice debt must be protected from usury or interest or other forms of deviation from sharia provisions. This study is intended to explain how Islam views the concept of foreign debt and domestic debt in the context of state debt. The approach used in this research is quantitative with literature study techniques. The results of the study show that in Islam foreign debt and domestic debt are things that are permissible or permissible provided that they are free from elements of usury or other things that are not in accordance with sharia provisions. Therefore, this is an important consideration for the state in making debts both for foreign debt and domestic debt. In addition, in carrying out debt, especially in making policies in the context of state debt, it must be based and reviewed from the urgency of the benefit for the community.Keywords: Debt; domestic debt; Foreign debt; Islamic Perspective;